A reflectometric interferometric nanosensor for sarcosine. (21st January 2015) - Diltemiz, Sibel Emir; Uslu, Okan
<x xml:space="preserve">Abstract</x> Sarcosine was recently identified as a differential metabolite that is present in urine in elevated concentration as prostate cancer develops metastases. The aim of this study is to prepare reflectometric interference spectroscopy (RIfS) nanosensors for the detection of sarcosine. Sarcosine imprinted nanoparticles were prepared by two phase miniemulsion polymerization and characterized with transmission electron microscopy, dynamic light scattering, and atomic force microscopy measurements. The glass substrates (10 × 10 mm2) were treated with Piranha solution and incubated in polyethyleneimine solution. The sarcosine imprinted nanoparticles were attached to glass substrates by spin coating of nanoparticle solution. The recognition properties of the nanosensors were evaluated by reflectometric interferometric spectroscopy. To show selectivity of sarcosine imprinted RIfS nanosensor, real‐time l‐alanine detection was also performed. Sarcosine detection studies were performed from aqueous solution and urine sample. A good linearity was revealed with a correlation coefficient of 0.9622 and a detection limit of 45 nM. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:55–61, 2015